Employment for poverty reduction and food security - von Braun, Joachim (International Food Policy Research Institute, 1995)
"Rapid expansion of employment in low-income countries is one of the biggest challenges of development. The growth in labor supply in developing countries will remain large for a long time to come. Incomes of the poor in rural areas will depend more and more on productive off-farm work, and in the rapidly expanding urban areas, food security will depend largely on jobs and wage rates"--P. xiii.